The Effect of Vitamin D on Intestinal Inflammation and Faecal Microbiota in Patients with Ulcerative Colitis. (3rd May 2018) - Garg, Mayur; Hendy, Philip; Ding, John Nik; Shaw, Sophie; Hold, Georgina; Hart, Ailsa
Abstract: Background and Aims: Vitamin D may be immunomodulatory and alter faecal microbiota, but results from clinical studies in humans to date have been inconclusive. This study aimed to assess the effect of vitamin D replacement in vitamin D-deficient patients with and without ulcerative colitis [UC] on inflammation and faecal microbiota. Methods: Vitamin D was replaced over 8 weeks in patients with active UC [defined by faecal calprotectin ≥ 100 µg/g], inactive UC [faecal calprotectin < 100 µg/g] and non-inflammatory bowel disease [IBD] controls with baseline serum 25[OH] vitamin D <50 nmol/l, and markers of inflammation and faecal microbiota were analysed. Results: Eight patients with active UC, nine with inactive UC and eight non-IBD controls received 40000 units cholecalciferol weekly for 8 weeks. Mean baseline 25[OH] vitamin D increased from 34 [range 12–49] to 111 [71–158] nmol/l [ p < 0.001], with no difference across the groups [ p = 0.32]. In patients with active UC, faecal calprotectin levels decreased from a median 275 to 111 µg/g [ p = 0.02], platelet count decreased [mean 375 to 313 × 10 9 /l, p = 0.03] and albumin increased [mean 43 to 45 g/l, p = 0.04]. These parameters did not change in patients with inactive UC or non-IBD controls. No changes in overall faecal bacterial diversity were noted although a significant increase in Enterobacteriaceae abundance was observed in patients with UC [ p = 0.03]. Conclusions: Vitamin D supplementation was associated with reduced intestinal inflammation in patients with active UC, with a concomitant increase in Enterobacteriaceae but no change in overall faecal microbial diversity.